Oral delivery of vancomycin by tetraether lipid liposomes - Uhl, Philipp; Pantze, Silvia; Storck, Philip; Parmentier, Johannes; Hofhaus, Götz; Mier, Walter; Fricker, Gert (European journal of pharmaceutical sciences, 2017)
Despite the outstanding progress in modern medicine, the oral delivery of peptide drugs is limited until today due to their instability in the gastrointestinal tract and low mucosa penetration. To overcome these hurdles, liposomes containing the specific tetraether lipid GCTE (glycerylcaldityltetraether lipid) were examined. For this purpose, the glycopeptide antibiotic vancomycin was used as model substance and liposomes were prepared by DAC (dual assymetric centrifugation). These liposomes showed a size and polydispersity index comparable to standard liposomes. A high encapsulation efficiency of 58.53±1.76% of the peptide drug vancomycin could be obtained as detected by HPLC. FCS analysis showed that in average each liposome contains 30 molecules of vancomycin. TEM and Cryo-EM micrographs verified the size and lamellarity of the liposomal formulations. Cytotoxicity tests in Caco-2 cells showed no significant cytotoxicity for all liposomal concentrations tested, indicating the good tolerability of these formulations. Furthermore, the use of sucrose as lyoprotector enabled the long term storage of the liposomal formulation for at least three months. The potency of this drug delivery system could be proven in an animal model using Wistar rats. One hour after oral application, 4.82±0.56% of the administered dose of vancomycin could be found in the blood as detected by immunoassay measurements. This transport did also not affect the integrity of the peptide as verified by immunoassay measurements. In combination with long term storage stability, this formulation appears to be a promising delivery system for oral application of peptide drugs.
Gesehen am 27.09.2018